(untitled) (Baghdad Science Journal, 2015)
Coronary artery disease (CAD) is a major health concern and leading of death in individuals with type 2 diabetes mellitus (T2DM). Glutathione S – Transferase(GST) are known for their broad range of detoxification and in the metabolism of xenobiotics . The role of functional variants of these genes in the development of various disorder is proven. We investigated the possible role of these variants in the development of CAD in T2DM patients. In this case – control study a total of 60 patients (T2DM = 30 ; T2DM – CAD = 30) and 30 controls were included. Serum lipid profiles were measured and DNA was extracted from the blood samples. Multiplex PCR for GSTT1/M1 (present / null) polymorphism, were performed for genotyping of study participants. Gene frequency and lipid profiles were statistically analyzed for disease association. Regression analysis showed that, there was no significant difference of the frequency of GSTT1 (positive /null) genotype and GSTM1 (positive /null) genotype in the 3 study groups . GSTT1 – positive genotype is associated with a 0.51 fold increased ( OR = 0.51 ; 95%CI = 2- 0.1 ;P = 0.321 ) , while the GSTM1 – positive genotype was associated with a 3 fold increase ( OR = 3.06 ; 95%CI=1- 9.7 ; P = 0.055) .We conclude GSTT1 positive genotype considered to be a protective risk from CAD in T2DM patients . The GSTM1 – positive genotype it was considered to be a risk factor of the CAD in T2DM patients.